One-step synthesis of Co2P/N-P co-doped porous carbon composites derived from soybean derivatives as acidic and alkaline HER electrocatalysts. (12th July 2022) - Jia, Shaopei; Cheng, Yifan; Huang, Quan; Li, Qisong; Zhang, Qian; Wang, Zhixin; Zhang, Yan; Zhang, Niu; Mu, Yunchao
Abstract: Developing inexpensive and efficient electrocatalysts for hydrogen evolution reaction (HER) in both acidic and alkaline mediums is of great significance to the hydrogen energy industry. Hereby, we prepared a mixture of precursors with homogeneous composition by using the chelating ability of soybean protein isolate (C and N source) and phytic acid (dopant and phosphating agent) with cobalt ions, and achieved one-step synthesis and construction of Co2 P/N–P co-doped porous carbon composite by carbonization at 800 °C. The as-synthesized Co2 P/NPPC-800 electrocatalyst exhibits low HER overpotentials of 121 and 125 mV at 10 mA cm −2 in 0.5 M H2 SO4 and 1.0 M KOH, which are close to those of the commercial Pt/C catalyst. Additionally, the NPPC substrate surrounding the Co2 P could diminish the corrosion during the HER, and Co2 P/NPPC-800 displays good stability and durability. Furthermore, this work offers a convenient synthesis strategy for phosphide/doped porous carbon composites in other electrochemical energy technologies. Graphical abstract: Image 1 Highlights: A new strategy achieved Co2 P/N–P co-doped porous carbon composite. The obtained Co2 P/NPPC exhibited good catalytic HER in alkaline and acidic mediums. The anchoring of Co2 P on the NPCC was beneficial for the stability and durability. The synthesis strategy was cost-effective, simple, eco-friendly and referenceable.